If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -21 + -18y + y = 13 Combine like terms: -18y + y = -17y -21 + -17y = 13 Solving -21 + -17y = 13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -17y = 13 + 21 Combine like terms: -21 + 21 = 0 0 + -17y = 13 + 21 -17y = 13 + 21 Combine like terms: 13 + 21 = 34 -17y = 34 Divide each side by '-17'. y = -2 Simplifying y = -2
| e^4x+2e^2x-24=0 | | 1000*q=1.4597 | | log81^1/9=x | | 3*-7-6y+y=13 | | 12p-15+6p=-27 | | 18x=x+y | | 0=-2x^2-10x | | Y=-0.3x-5.3 | | 2x^2+2x+25=289 | | 3ab-ab+b= | | 96+.18x+.20x=376 | | 6/x^2 | | 3(-7-6y)-y=13 | | 6x+10=35-9x | | 18-x+x+14-x+5=36 | | 2x^2-31x-475=0 | | 5/6x-4/5=0 | | x=3(13/6)-9 | | 2x-10+3x-5=90 | | 2x^2-30x-475=0 | | 7=x^2-32 | | 2(19-3y)=10 | | 4-(7x-3)=5 | | 2d+5=20-3e | | (42)(6)=(x)(32-x) | | x-8.1=5.33 | | 4x+6=-54-6 | | -2/3x-5=-1 | | P=pw | | x+5-2=1 | | X+(x*.6)=265 | | -20(x-5)=-120 |